Analysis of the Copyright Dispute Decision Between Djanuar Ishak and PT. Elang Prima Retailindo: Study Of Commercial Court Decision Number 35/PDT.SUS-COPYRIGHT/2021/PN JKT.PUS - Kartiko, Nafis Dwi; Soegiono, Samuel Putra (Journal of Legal and Cultural Analytics, 2024)
This research aims to analyze the legal aspects involved in copyright protection in Indonesia and provide recommendations for the improvement of copyright protection, particularly regarding copyright enforcement in the use of works for advertising purposes without permission. Using a normative-doctrinal juridical approach, this research investigates the legal framework governing copyright in Indonesia through a systematic analysis of relevant legislation, principles and rules of law. The research focuses on the internal assessment of Indonesian positive law by exploring the prevailing legal conceptions and principles, examining Case Number 35/Pdt.Sus-Copyright/2021/PN Jkt.Pst as the main case study. The results show the importance of the state in protecting intellectual property rights to maintain dignity and respect for individual works. This research is expected to enrich the intellectual property law literature and increase public awareness and understanding of the importance of asking permission to creators when using their works, as well as encourage the government and relevant institutions to take concrete steps to strengthen copyright protection.